LANGUAGE DIDACTICS: THE SHIFT OF PARADIGMS IN LANGUAGE DEVELOPMENT AND THE LOGIC OF LANGUAGE TEACHING AND LEARNING - Nauckūnaitė, Zita (Acta Paedagogica Vilnensia, 2015)
The paper provides an analysis of the linguistic aspect of language didactics. The Lithuanian language syllabi of the basic school are studied against the background of linguistic paradigms with the purpose of establishing the following: 1) how the shift of linguistic paradigms affects the changes in the paradigm of language development, and 2) what particular changes in the awareness of language system have taken place with regard of different language development paradigms.Three linguistic paradigms have been taken into consideration: 1) comparative-historical, 2) structural, and 3) anthropocentric. The latter two correlate well with the language development paradigms in Lithuanian schools. The analysis proves that in the period of 1909 to 1993, the syllabi of the Lithuanian language followed the systemic paradigm of language development with structural linguistic and classical development paradigms at their basis. The syllabi of the Lithuanian language for 1994 to 2008 were designed according to the communicative-integral language development paradigm based on the anthropocentric paradigm of linguistics and free development paradigm.Both language development paradigms have their merits and shortcomings. The advantage of the systemic paradigm is linguistic and logical reasoning, whereas communicative integral paradigm enhances the development of free linguistic communication. The principal disadvantage of the systemic paradigm is grammatization and formalization, and the shortcoming of the communicative-integral paradigm is its fragmentariness and indefiniteness.At present the Lithuanian language syllabi for primary and basic education are being updated with the aim of retaining the best qualities of both syllabi: systematic teaching of the Lithuanian language, thematic/chronological teaching of literature, and more intensive training in the use of spoken and written language. The new syllabus of the Lithuanian language development is based on synergy as a new modern paradigm.
Keywords: language development paradigm; basic education; Lithuanian language syllabi; linguistic paradigms; synergy